Strategi Pembelajaran Tahfiz Al-Qur’an Di Mas Miftahussalam Medan - Dheria Rahima; Nanda Rahayu Agustia; Tumiran Tumiran (Journal Of Dehasen Educational Review, 2026)
This study analyzes Al-Qur’an tahfiz learning strategies to enhance memorization quality at MAS Miftahussalam Medan. Employing a qualitative case study design, data were collected through interviews, observations, and documentation. The findings identify three core strategies: (1) optimizing morning "golden hours" for routines; (2) implementing flexible targets prioritizing quality over quantity to support students' psychological well-being; and (3) strengthening independent murojaah before submission. These strategies are structured through Control Cards for monitoring and Tahfiz Graduation for appreciation. Supporting factors include a conducive madrasa environment, while primary obstacles involve limited recitation time, physical fatigue from heavy academic workloads, and inconsistent home revision. In conclusion, while the implemented strategies effectively maintain memorization consistency and quality, further improvements in time management and disciplined motivation are essential to overcome prevailing academic challenges.